Remembering the Past: The Collective Memory and Historigraphies of Cyprus - Çiftçi, Dilan (Journal of History Culture and Art Research, 2018)
The aim of this study is to investigate the politics of memory and the transformations of memories of historiographies in the Cyprus Conflict. I focus on the collective memory conceptualization that invades Cyprus Conflict, and I investigate Cyprus history textbooks from Greek Cypriot and Turkish Cypriot education system. In this regard, the Turkish Cypriot and Greek Cypriot memories are mostly based on the historiographies, negative memories of between 1958s and 1963s and the heroic partisan struggle strongly clash with negative counter-memories of 1974. The forced remembering of 1974, the Greek Cypriots and Turkish Cypriots, which is promoted also by politically institutionalized top-down politics of memory, is created also in the popular, bottom-up memories of the today's negotiations. Such memory politics foster past narratives mostly based on historiographies, creates us and them dichotomy narratives. Moreover, it blurs the negotiation and forgiveness paradigm, when it suddenly becomes the certain point of collective memory of past and present.